Effects of Packaging on Germination and Storability of Soybean Seed under Ambient Condition - V.S. GIRASE; V.D. SHENDE; A.D. DUMBRE; R.S. SHAIKH (Seed Research, 2026)
An experiment was conducted to study the impact of packaging material on germination and storability of soybean seed variety JS-335 under ambient storage conditions at farmer’s level during 2002-03 and 2003-04. All the parameters showed significant difference due to packaging and seed sources. Germination and field emergence from seed stored in Poly-lined Jute Canvas (PL-JC) bag were higher as compared to Jute Canvas (JC) bag during 8 months from storage. Moisture content in seeds stored in PL-JC bag was maintained, whereas, it increased in seeds stored in JC bag. Electrical conductivity of seed leachate increased steadily with increase in storage period. It increased sharply in the seeds stored in JC bag, whereas, seeds stored in PL-JC bag recorded much lower increment in the seed leachate. These results suggest that the PL-JC bags are superior to the JC bag for storage of soybean seed.